Experimental investigation of a vertical round free turbulent jet - Zayan, Jalal Mohammad; Asrar, Waqar; Hoda, Asif (2013)
An experimental investigation of the flow in a vertical round free turbulent jet has been carried out. This study attempts to map the Reynolds stresses and to determine the differences in mean velocity profiles, turbulence intensity profiles, and velocity spectra in the flow of a vertical round free jet at room conditions. Constant Temperature Anemometry (CTA) using 1D probe was used to measure the, mean and fluctuating velocity components to obtain the Reynolds stress correlations. The results agree with published data. The exit conditions of the jet play a very important role in the development of the jet in the near field but the far field flow remains independent of the exit conditions of the jet. Keywords-Keywords-Turbulent Jet; Reynolds number; Hot wire Anemometry; Reynolds Stresses